Pengaruh Risk Tolerance dan Religiusitas terhadap Keputusan Investasi dengan Literasi Keuangan sebagai Variabel Moderasi - Idhofi Khusna Baihaqqi; Maretha Ika Prajawati (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The purpose of this study is to determine the effect of risk tolerance and religiosity on direct investment decisions, as well as the effect of either moderated or unmoderated by financial literacy. Quantitative research with a descriptive approach is the type of research in this study. The population of this study were active students of the Faculty of Economics, Maulana Malik Ibrahim State Islamic University, Malang. Meanwhile, the sample of this research is 100 students who invest in the capital market selected by purposive sampling technique and Slovin formula. The research data this time is primary data tested using SmartPLS 3 software with analytical techniques in the form of descriptive statistics, outer models, and inner models. The results of this study indicate that there is a positive and significant influence of religiosity and financial literacy on investment decisions, while risk tolerance has no effect on investment decisions. In addition, it was also found that the role of financial literacy in moderating the relationship between religiosity and investment decisions, but failed to moderate the relationship between risk tolerance and investment decisions.